High-safety emulsion explosive and production process thereof

CN118619798BActive Publication Date: 2026-10-27HEBEI XINGUANG CHEM IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410952278.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-16
Publication Date
2026-10-27
Estimated Expiration
2044-07-16

AI Technical Summary

Technical Problem

[0004]在现有技术中,经过研究已经公开了水相材料的内相粒径越小,则乳胶基质的抗老化性能越优异的结论,因此,在现有的生产工艺中,往往将硝酸铵通过处理转变为纳米级别的超细颗粒后进行使用,同时在水相中增加聚合物化学材料来增强硝酸铵的溶解性进而降低硝酸铵的析晶率,以防止炸药性能变差,但是,为了避免聚合物过度影响炸药的性质,对其添加量具有一定的限制,因此其效果相当微小,虽然可以在现有基础的程度上略微提高炸药的稳定性,但是提升力度仍有待提高

Benefits of technology

1、本发明的高安全性乳化炸药中,在乳胶基质中加入了改性疏水性气相二氧化硅,其为内部含水、表观状态为固态壳体粉末状的胶囊结构粉体,外壳与液体水之间的结合强度不算太高,在高温或撞击状态下,会导致结合结构的破坏,进而使得外壳中的液体水被释放出来,从而可以增加硝酸铵的溶解度,降低硝酸铵的表面活性,防止硝酸铵产生析晶现象,同时,硝酸铵在溶解时需要吸热,可以进一步降低高温对乳胶基质的影响。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a kind of high security emulsion explosive and production process thereof, it is related to emulsion explosive technical field, including the following mass fraction of raw materials: ammonium nitrate 70-75%, sodium nitrate 2-4%, phosphoric acid 0.1-0.2%, water 16-20%, modified hydrophobic fumed silica 0.3-0.5%, composite oil phase material 6-8%, sensitizer 0.05-0.15%, wherein the preparation method of modified hydrophobic fumed silica is: the hydrophobic fumed silica and water of weight ratio 1:(15-20) are added to high-speed dispersion machine with 500-800rpm stirring 55-70s, and the modified hydrophobic fumed silica with particle size of 10-25 μm is obtained;The high security emulsion explosive of the application has stronger performance stability and safety by adding modified hydrophobic fumed silica and adding polyisoprene in oil phase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of emulsion explosives technology, specifically to a high-safety emulsion explosive and its production process. Background Technology

[0002] Emulsion explosives, a type of water-in-oil latex explosive, have become one of the main types of industrial explosives in my country due to their simple production process, excellent explosive performance, and wide range of applications. Emulsion explosives consist of three parts: an aqueous phase, an oil phase, and a sensitizer. The aqueous and oil phases are blended to form the latex matrix, while the sensitizer is used to adjust the density of the explosive to improve its performance and meet operational requirements. In certain specialized fields, in addition to the sensitizer, specific additives are added to the emulsion explosive to further adjust its explosive properties and meet operational requirements.

[0003] Because the latex matrix is ​​a thermodynamically unstable system, it may be damaged during high-speed shear emulsification, transportation vibration, pipeline pumping, and storage, leading to oil-water phase separation, causing ammonium nitrate crystallization, and ultimately resulting in a decrease in the performance of the mixed emulsion explosive, or even mis-detonation. To ensure the stability and detonation performance of the mixed emulsion explosive, and to withstand the bumps and vibrations of long-distance transportation, the latex matrix must have high emulsification efficiency and good dispersibility during preparation.

[0004] In existing technologies, research has revealed that the smaller the internal phase particle size of aqueous materials, the better the anti-aging performance of the latex matrix. Therefore, in current production processes, ammonium nitrate is often processed into nano-sized ultrafine particles before use. At the same time, polymer chemical materials are added to the aqueous phase to enhance the solubility of ammonium nitrate and reduce its crystallization rate, thereby preventing the explosive performance from deteriorating. However, in order to avoid the polymer from excessively affecting the properties of the explosive, there are certain limitations on its addition amount, so its effect is quite small. Although it can slightly improve the stability of the explosive to the existing extent, the improvement still needs to be improved. Summary of the Invention

[0005] The purpose of this invention is to provide a highly safe emulsion explosive and its production process; and to solve the following technical problems: How to efficiently improve the stability of emulsion explosive performance? The objective of this invention can be achieved through the following technical solutions: In a first aspect, the present invention discloses a high-safety emulsion explosive comprising the following raw materials in the following mass fractions: ammonium nitrate 70-75%, sodium nitrate 2-4%, phosphoric acid 0.1-0.2%, water 16-20%, modified hydrophobic fumed silica 0.3-0.5%, composite oil phase material 6-8%, and sensitizer 0.05-0.15%; the sum of the mass fractions of the raw materials is 100%.

[0006] Preferably, the raw materials include the following mass fractions: ammonium nitrate 72-74%, sodium nitrate 3-4%, phosphoric acid 0.15-0.2%, water 17-19%, modified hydrophobic fumed silica 0.4-0.5%, composite oil phase material 6-7.5%, and sensitizer 0.1-0.15%; More preferably, the raw materials include the following mass fractions: 73.2% ammonium nitrate, 3% sodium nitrate, 0.15% phosphoric acid, 17% water, 0.5% modified hydrophobic fumed silica, 6% composite oil phase material, and 0.15% sensitizer.

[0007] In a further embodiment of the present invention, the method for preparing modified hydrophobic fumed silica is as follows: Hydrophobic fumed silica and water in a weight ratio of 1:(15-20) are added to a high-speed disperser and stirred at 500-800 rpm for 55-70 s to obtain modified hydrophobic fumed silica with a particle size of 10-25 μm; wherein, the weight ratio is preferably 1:(16-19), more preferably 1:18.

[0008] Preferably, the hydrophobic fumed silica is fumed silica HB-630.

[0009] Hydrophobic fumed silica self-assembles into a solid shell under the influence of surface tension and electrostatic force of droplets, encapsulating liquid water and ultimately forming a capsule-like powder containing water on the inside and appearing as a solid powder. Since only 500-800 rpm is used for dispersion and the stirring time is only 55-70 seconds, the bonding strength between the shell and the liquid is not very high. Under high temperature or impact conditions, the bonding structure will be destroyed, thus releasing the liquid water in the shell.

[0010] In a further embodiment of the present invention: the composite oil phase material comprises diesel oil, Span-80 emulsifier and polyisoprene, wherein the mass fraction ratio of the three is (50-60%):(25-30%):(10-25%).

[0011] In a further embodiment of the present invention, the composite oil phase material is prepared by sequentially adding diesel oil, Span-80 emulsifier and polyisoprene into a stirrer and stirring evenly at a temperature below 30°C to obtain the composite oil phase material.

[0012] Polyisoprene has a long-chain polymer structure. When combined with Span-80 emulsifier, its derived functional groups and long-chain alkyl groups bond together, which can improve the strength of the oil phase material.

[0013] In a further embodiment of the present invention: the sensitizer is prepared by mixing sodium nitrite, sodium chloride and water in a mass ratio of (2-3):(1-2):(9-10) at 40°C to obtain the sensitizer; wherein, the preferred mass ratio is 2:1:9.

[0014] Secondly, the present invention also discloses a production process for a high-safety emulsion explosive as described above, comprising the following steps: Step 1: Grind sodium nitrate and add it together with ammonium nitrate, sodium nitrate and water into a stirrer and stir evenly at 80-100℃ to obtain an aqueous phase material; Step 2: Heat the aqueous phase material, composite oil phase material and modified hydrophobic fumed silica together and add them into an emulsifier. Stir at high speed at 30-35℃ to obtain a latex matrix. Step 3: Add sensitizer to the latex matrix and continue stirring until foaming is uniform to obtain sensitized latex; Step 4: The sensitized latex is sent to the packaging workshop for packaging to obtain highly safe emulsion explosives.

[0015] In a further embodiment of the present invention: in the first step, the grinding step of the sodium nitrate is as follows: first, the sodium nitrate is placed in a ball mill for preliminary grinding, and then transferred to an air jet mill for fine grinding. During the grinding process, a particle size analyzer is used to monitor the particle size distribution of the sodium nitrate, and the grinding parameters are adjusted as needed. Finally, the sodium nitrate is sieved using a sieve to ensure that the obtained sodium nitrate particle size is less than 5 μm.

[0016] The crystallization process of ammonium nitrate includes two parts: crystal nucleus formation and crystal growth. The formation of crystal nuclei will generate cohesive forces inside the droplet, while the growth of crystals will destroy the interfacial film of the droplet and cause crystallization. The smaller the particle size of ammonium nitrate in the aqueous phase, the more difficult it is for crystal nuclei to form. Therefore, when affected by the external environment, less aggregation occurs in its internal phase, and the crystallization phenomenon is alleviated, which is conducive to reducing the crystallinity of the latex matrix and improving its stability.

[0017] In a further embodiment of the present invention: in the second step, the stirring speed of the emulsifier is 1200-1600 rpm, and the stirring time is 60-80 s; Preferably, the stirring speed of the emulsifier is 1400-1600 rpm, and more preferably, the stirring speed of the emulsifier is 1600 rpm.

[0018] In a further embodiment of the present invention: in the third step, the sensitizer is added in 2-3 portions, with an interval of 5-10 minutes between each addition, a stirring rate of 1000-1200 rpm, and a temperature of 35-45°C.

[0019] Sensitization can be used to adjust the density of the latex matrix to match the charge density.

[0020] In a further embodiment of the present invention: in the fourth step, the sensitized latex is packaged in a plastic film as a pill roll.

[0021] The beneficial effects of this invention are: 1. In the high-safety emulsion explosive of the present invention, modified hydrophobic fumed silica is added to the latex matrix. It is a capsule-structured powder containing water inside and appearing as a solid shell powder. The bonding strength between the shell and the liquid water is not very high. Under high temperature or impact, the bonding structure will be destroyed, thereby releasing the liquid water in the shell. This can increase the solubility of ammonium nitrate, reduce the surface activity of ammonium nitrate, and prevent the crystallization of ammonium nitrate. At the same time, ammonium nitrate requires endothermic dissolution, which can further reduce the impact of high temperature on the latex matrix.

[0022] 2. In the high-safety emulsion explosive of the present invention, modified hydrophobic fumed silica is added to the latex matrix. After the water inside is released, the hydrophobic fumed silica remains in the latex matrix as an inert material, acting as a shell. Due to its porous structure, it has a low packing density and occupies a large amount of space in the emulsion explosive at a low mass fraction, i.e., a high volume fraction. Therefore, it can significantly reduce the energy density of the emulsion explosive, reduce its detonation velocity, avoid easy explosion during transportation and impact, and improve its safety performance.

[0023] 3. In the high-safety emulsion explosive of the present invention, modified hydrophobic fumed silica is added to the latex matrix. After the water inside is released, the hydrophobic fumed silica remains in the latex matrix as an inert material, acting as a shell. When ammonium nitrate generates crystal nuclei, the nuclei grow into crystals at the oil film interface. At this time, the shell can prevent some crystals from penetrating the oil film and causing crystallization. At low temperatures, the water inside the modified hydrophobic fumed silica will not be released, but it can still prevent crystals from penetrating to the outside of the oil film. Therefore, the crystallization rate can be further reduced and its stability improved.

[0024] 4. In the high-safety emulsion explosive of the present invention, polyisoprene is added to the composite oil phase material of the latex matrix. Polyisoprene has a long-chain polymer structure. After being combined with Span-80 emulsifier, its derived functional groups and long-chain alkyl groups are bonded to each other, which can improve the strength of the oil phase material and provide steric protection for the aqueous phase molecules, thereby improving the stability of the latex matrix. At the same time, the molecular chains of polyisoprene can interact with the molecular chains in the oil film to form a more stable network structure, giving the oil film better elasticity. Therefore, when crystals in the aqueous phase grow and extend into the oil film, the oil film can deform under the action of elasticity to resist crystal precipitation, thereby reducing the crystallization rate of the emulsion explosive and improving its stability. Detailed Implementation

[0025] The present invention will now be described in further detail with reference to specific embodiments. The given embodiments are merely illustrative of the invention and not intended to limit its scope. The embodiments provided below can serve as a guide for further improvements by those skilled in the art and do not constitute a limitation on the invention in any way.

[0026] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Unless otherwise specified, the materials and reagents used in the following examples are commercially available.

[0027] Example 1 Preparation of modified hydrophobic fumed silica: Hydrophobic fumed silica HB-630 and water were added together in a weight ratio of 1:18 into a high-speed disperser. The speed of the high-speed disperser was set to 600 rpm and the stirring time was 60 s. After the stirring time was completed, modified hydrophobic fumed silica was obtained. The particle size was measured and found to be within 10-25 μm, with an average particle size of 18 μm.

[0028] Example 2 Preparation of composite oil phase materials: Diesel fuel, Span-80 emulsifier, and polyisoprene in a mass fraction ratio of 55%:30%:15% were added to a mixer in sequence. The internal temperature of the mixer was set to 25°C, the speed to 600 rpm, and the mixing time to 120 s. After mixing, the upper layer of foam was skimmed off to obtain the composite oil phase material.

[0029] Example 3 Preparation of composite oil phase materials: Diesel fuel and Span-80 emulsifier in a mass fraction ratio of 55%:30% were added to the mixer in sequence. The internal temperature of the mixer was set to 25℃, the speed to 600rpm, and the mixing time to 120s. After mixing, the upper layer of foam was skimmed off to obtain the composite oil phase material.

[0030] Example 4 Preparation of sensitizer: Sodium nitrite, sodium chloride, and water in a mass ratio of 2:1:9 were added to a stirrer. The stirrer temperature was set to 35°C, the stirring speed to 600 rpm, and the stirring time to 200 s. After stirring, the sensitizer was prepared.

[0031] Example 5 Preparation of highly safe emulsion explosives: Prepare 70% ammonium nitrate, 4% sodium nitrate, 0.2% phosphoric acid, 17.35% water, 0.3% modified hydrophobic fumed silica prepared in Example 1, 8% composite oil phase material prepared in Example 2, and 0.15% sensitizer prepared in Example 4 by mass fraction. Ammonium nitrate was ground to a particle size of less than 5 μm using a ball mill and an air jet mill. The ground ammonium nitrate, sodium nitrate, and water were then added to a stirrer. The stirrer temperature was set to 80°C and the stirring time to 5 min. After stirring, an aqueous phase material was obtained. The aqueous phase material, composite oil phase material, and modified hydrophobic fumed silica, cooled to room temperature, were then added to an emulsifier. The emulsifier speed was set to 1200 rpm, the temperature to 30°C, and the stirring time to 80 s. After stirring, a latex matrix was obtained. A sensitizer was added to the latex matrix in the emulsifier in two separate additions, with the same amount added each time and a 10 min interval between additions. The emulsifier speed was set to 1000 rpm, the temperature to 35°C, and the stirring time to 30 min. After stirring, a sensitized latex was obtained. The sensitized latex was then sent to the packaging workshop and packaged in plastic film into explosive rolls, thus obtaining a high-safety emulsion explosive.

[0032] Example 6 Preparation of highly safe emulsion explosives: Prepare 71% ammonium nitrate, 3.5% sodium nitrate, 0.15% phosphoric acid, 17% water, 0.35% modified hydrophobic fumed silica prepared in Example 1, 7.85% oil-phase composite material prepared in Example 2, and 0.15% sensitizer prepared in Example 4 by mass fraction. Ammonium nitrate was ground to a particle size of less than 5 μm using a ball mill and an air jet mill. The ground ammonium nitrate, sodium nitrate, and water were then added to a stirrer. The stirrer temperature was set to 85°C, and the stirring time was 4.5 min. After stirring, an aqueous phase material was obtained. The aqueous phase material, composite oil phase material, and modified hydrophobic fumed silica, cooled to room temperature, were added to an emulsifier. The emulsifier speed was set to 1400 rpm, the temperature to 32°C, and the stirring time to 70 s. After stirring, a latex matrix was obtained. A sensitizer was added to the latex matrix in the emulsifier in two separate additions, with the same amount added each time and a 10 min interval between additions. The emulsifier speed was set to 1100 rpm, the temperature to 40°C, and the stirring time to 25 min. After stirring, a sensitized latex was obtained. The sensitized latex was then sent to the packaging workshop and packaged in plastic film into explosive rolls, thus obtaining a high-safety emulsion explosive.

[0033] Example 7 Prepare ammonium nitrate (72.3% by mass), sodium nitrate (3% by mass), phosphoric acid (0.15% by mass), water (18% by mass), modified hydrophobic fumed silica (0.4% by mass) prepared in Example 1, oil-phase composite material (6% by mass) prepared in Example 2, and sensitizer (0.15% by mass) prepared in Example 4. Ammonium nitrate was ground to a particle size of less than 5 μm using a ball mill and an air jet mill. The ground ammonium nitrate, sodium nitrate, and water were then added to a stirrer. The stirrer temperature was set to 90°C and the stirring time to 4 min. After stirring, an aqueous phase material was obtained. The aqueous phase material, composite oil phase material, and modified hydrophobic fumed silica, cooled to room temperature, were added to an emulsifier. The emulsifier speed was set to 1600 rpm, the temperature to 35°C, and the stirring time to 60 s. After stirring, a latex matrix was obtained. A sensitizer was added to the latex matrix in the emulsifier in three separate additions at 6 min intervals. The emulsifier speed was set to 1200 rpm, the temperature to 45°C, and the stirring time to 20 min. After stirring, a sensitized latex was obtained. The sensitized latex was then sent to the packaging workshop and packaged in plastic film into explosive rolls to obtain a high-safety emulsion explosive.

[0034] Example 8 Prepare 73% ammonium nitrate, 3% sodium nitrate, 0.15% phosphoric acid, 17.25% water, 0.45% modified hydrophobic fumed silica prepared in Example 1, 6% oil-phase composite material prepared in Example 2, and 0.15% sensitizer prepared in Example 4 by mass fraction. Ammonium nitrate was ground to a particle size of less than 5 μm using a ball mill and an air jet mill. The ground ammonium nitrate, sodium nitrate, and water were then added to a stirrer. The stirrer temperature was set to 95°C, and the stirring time was 3.5 min. After stirring, an aqueous phase material was obtained. The aqueous phase material, composite oil phase material, and modified hydrophobic fumed silica, cooled to room temperature, were added to an emulsifier. The emulsifier speed was set to 1600 rpm, the temperature to 35°C, and the stirring time to 60 s. After stirring, a latex matrix was obtained. A sensitizer was added to the latex matrix in the emulsifier in three separate additions at 6 min intervals. The emulsifier speed was set to 1200 rpm, the temperature to 45°C, and the stirring time to 20 min. After stirring, a sensitized latex was obtained. The sensitized latex was then sent to the packaging workshop and packaged in plastic film into explosive rolls to obtain a high-safety emulsion explosive.

[0035] Example 9 Prepare ammonium nitrate (74.75%), sodium nitrate (2.5%), phosphoric acid (0.1%), water (16%), modified hydrophobic fumed silica (0.5%) prepared in Example 1, oil-phase composite material (6%) prepared in Example 2, and sensitizer (0.15%) prepared in Example 4 by mass fraction. Ammonium nitrate was ground to a particle size of less than 5 μm using a ball mill and an air jet mill. The ground ammonium nitrate, sodium nitrate, and water were then added to a stirrer. The stirrer temperature was set to 100℃ and the stirring time to 3 min. After stirring, an aqueous phase material was obtained. The aqueous phase material, composite oil phase material, and modified hydrophobic fumed silica, cooled to room temperature, were added to an emulsifier. The emulsifier speed was set to 1600 rpm, the temperature to 35℃, and the stirring time to 60 s. After stirring, a latex matrix was obtained. A sensitizer was added to the latex matrix in the emulsifier in three separate additions at 6 min intervals. The emulsifier speed was set to 1200 rpm, the temperature to 45℃, and the stirring time to 20 min. After stirring, a sensitized latex was obtained. The sensitized latex was then sent to the packaging workshop and packaged in plastic film into explosive rolls to obtain a high-safety emulsion explosive.

[0036] Comparative Example 1 The only difference from Example 7 is that no modified hydrophobic fumed silica is added during preparation.

[0037] Comparative Example 2 The only difference from Example 7 is that the modified hydrophobic fumed silica is replaced with hydrophobic fumed silica HB-630.

[0038] Comparative Example 3 The only difference from Example 7 is that the composite oil phase material prepared in Example 2 is replaced with the composite oil phase material prepared in Example 3.

[0039] Comparative Example 4 The only difference from Example 7 is that modified hydrophobic fumed silica is not added during preparation and the composite oil phase material obtained in Example 2 is replaced with the composite oil phase material obtained in Example 3.

[0040] The high-safety emulsion explosives prepared in Examples 5-9 and Comparative Examples 1-4 were subjected to high- and low-temperature cyclic storage tests. The test method was as follows: The programmable high and low temperature chamber was programmed with temperature cycling. The environmental conditions were 40°C for 16 hours and -10°C for 8 hours, with each cycle lasting 24 hours. One roll of each of the high-safety emulsion explosives prepared in Examples 5-9 and Comparative Examples 1-4 was placed in the programmable high and low temperature chamber when the temperature reached 40°C. After 0-4 cycles of storage, the packaging of the emulsion explosives was removed, and the sensitized latex inside the plastic film was taken out for study and testing, including the following tests: (1) Particle size test After each storage cycle, 5g of sensitized latex was taken from each group of emulsion explosive packages. After standing at room temperature, it was dispersed with 100mL of diesel oil, and the surface area, volume, and particle size range were measured using a laser particle size analyzer. The test results are listed in Table 1, as follows: Table 1

[0041] (2) Microstructure testing After each storage cycle, 5g of sensitized latex was taken from each group of emulsion explosive packages. After standing to room temperature, it was placed in a beaker and diluted with diesel oil. After mixing evenly, an appropriate amount of sample was dropped onto a glass slide that had been soaked in dilute hydrochloric acid to remove dirt and dried. The sample was evenly dispersed with a glass rod, covered with a coverslip, and the microstructure of the matrix was observed under a microscope. The test results are listed in Table 2. Table 2 is as follows: Table 2

[0042] (3) Crystallization amount test After each storage cycle, 20g of sensitized latex from each group of emulsion explosive packages was spread evenly in a petri dish. The petri dish was placed in a beaker and 180mL of water was added. The mixture was allowed to stand at room temperature for 24 hours. Using a graduated cylinder, 25mL of the solution from the beaker and 10mL of formaldehyde solution were transferred to an Erlenmeyer flask. 2-3 drops of phenolphthalein indicator were added, and the solution was titrated with 0.01mol / L sodium hydroxide solution. The titration was performed twice, and the average value was taken. The ammonium ions in the solution reacted with formaldehyde to produce hexamethylenetetramine and an equal amount of nitric acid. The content of ammonium nitrate could be calculated by titrating the generated nitric acid with sodium hydroxide solution. Based on the amount of sodium hydroxide consumed, the amount of ammonium nitrate crystals could be calculated. The test results are listed in Table 3. Table 3 is as follows:

[0043] Analysis of the data in Tables 1-3 shows that, compared with Comparative Examples 1-4, the emulsion explosives prepared in Examples 5-9 exhibited significantly lower particle size changes, significantly lower microstructure changes, and significantly less crystallization after each cycle of high and low temperature cycling tests. This indicates that the high-safety emulsion explosives of the present invention have stronger stability and safety.

[0044] The foregoing has provided a detailed description of one embodiment of the present invention, but this description is merely a preferred embodiment and should not be construed as limiting the scope of the invention. All equivalent variations and modifications made within the scope of the claims of this invention should still fall within the patent coverage of this invention.

Claims

1. A highly safe emulsion explosive, characterized in that, The raw materials include the following components by mass fraction: ammonium nitrate 70-75%, sodium nitrate 2-4%, phosphoric acid 0.1-0.2%, water 16-20%, modified hydrophobic fumed silica 0.3-0.5%, composite oil phase material 6-8%, and sensitizer 0.05-0.15%. The sum of the mass fractions of the raw materials is 100%; The method for preparing the modified hydrophobic fumed silica is as follows: Hydrophobic fumed silica and water in a weight ratio of 1:(15-20) are added to a high-speed disperser and stirred at 500-800 rpm for 55-70 s to obtain modified hydrophobic fumed silica with a particle size of 10-25 μm. The composite oil phase material includes diesel oil, Span-80 emulsifier and polyisoprene, with a mass fraction ratio of (50-60%):(25-30%):(10-25%).

2. The high-safety emulsion explosive according to claim 1, characterized in that, The method for preparing the composite oil phase material is as follows: diesel oil, Span-80 emulsifier and polyisoprene are added to a stirrer in sequence and stirred evenly at a temperature below 30°C to obtain the composite oil phase material.

3. The high-safety emulsion explosive according to claim 1, characterized in that, The sensitizer is prepared by mixing sodium nitrite, sodium chloride and water in a mass ratio of (2-3):(1-2):(9-10) at 40°C until homogeneous.

4. A production process for a high-safety emulsion explosive as described in any one of claims 1-3, characterized in that, Includes the following steps: Step 1: Grind ammonium nitrate and add it together with sodium nitrate and water into a stirrer and stir evenly at 80-100℃ to obtain an aqueous phase material; Step 2: Heat the aqueous phase material, composite oil phase material and modified hydrophobic fumed silica together and add them into an emulsifier. Stir at high speed at 30-35℃ to obtain a latex matrix. Step 3: Add sensitizer to the latex matrix and continue stirring until foaming is uniform to obtain sensitized latex; Step 4: The sensitized latex is sent to the packaging workshop for packaging to obtain highly safe emulsion explosives.

5. The production process of the high-safety emulsion explosive according to claim 4, characterized in that, In the first step, the grinding steps of the ammonium nitrate are as follows: first, the ammonium nitrate is placed in a ball mill for preliminary grinding, and then transferred to an air jet mill for fine grinding. During the grinding process, a particle size analyzer is used to monitor the particle size distribution of the ammonium nitrate. The grinding parameters are adjusted as needed. Finally, the ammonium nitrate is sieved using a sieve to ensure that the obtained ammonium nitrate particle size is less than 5μm.

6. The production process of the high-safety emulsion explosive according to claim 4, characterized in that, In the second step, the stirring speed of the emulsifier is 1200-1600 rpm, and the stirring time is 60-80 s.

7. The production process of the high-safety emulsion explosive according to claim 4, characterized in that, In the third step, the sensitizer is added in 2-3 portions, with an interval of 5-10 minutes between each addition, at a stirring speed of 1000-1200 rpm and a temperature of 35-45℃.

8. The production process of the high-safety emulsion explosive according to claim 4, characterized in that, In the fourth step, the sensitized latex is packaged in plastic film as a pill roll.

Citation Information

Patent Citations

  • Preparation method of safe diesel oil with flame-retardant explosion suppression function

    CN105733700A

  • Hydrophobic fumed silica water-dispersible sol and preparation method thereof

    CN116143130A